History of the world in 1,000 objects - Bryant, Lili; Majithia, Manisha; Setford, Steve; Shang, Kaiya; Wolter, Debra; Lee, Suefa (Dorling Kindersley Limited, 2014)
Look at world history, viewing cultures and early civilizations through the objects that they created. From a Viking wooden comb to a 1950s fridge-freezer, this title helps you uncover what the people's priorities were at the time from what they created.